The Photographic Object 1970 - Statzer, Mary, 1966- (Book collections on Project MUSE., 2016)
"In 1970 photography curator Peter C. Bunnell organized an exhibition called 'Photography into Sculpture' for the Museum of Modern Art, New York. The project, which brought together twenty-three photographers and artists from the United States and Canada, was among the first exhibitions to recognize work that blurred the boundaries between photography and other mediums. At once an exhibition catalogue after the fact, an oral history, and a critical reading of exhibitions and experimental photography during the 1960s and 1970s, 'The Photographic Object 1970' proposes precedents for contemporary artists who continue to challenge traditional practices and categories."--Provided by publisher